Performance Of Tomato (Solanum Lycopersicum L.) Genotypes Under Naturally Ventilated Polyhouse In Kumaon Hills Of Uttarakhand (India) (Applied Biological Research, 2020)
This study was aimed to assess the performance of various tomato genotypesunder ventilated poly-house conditions. The study was conducted inKumaun hills of Uttarakhand (India) during summer 2017. The studyrevealed the presence of high genotypic and high heritability for moseconomic traits viz., number of fruits plant-1, yield plant-1,ascorbic acidcontent and total antioxidant activities. The variety ‘VL-4’ proved superiorover other varieties with respect to fruit length (5.43 cm), fruit width (5.27cm), number of fruits plant-1(51.67), average fruit weight (85.34 g) and fruityield plant-1(4.42 kg). Highest luminous (L*= 49.96), TSS (6.03oB), reducingsugar (1.99%) and total sugar (3.39%) were estimated in genotype ‘H-86’;whereas highest red colour (a*= 42.43) and total antioxidant activity (28.06mMTE L-1) were found in hybrid ‘Dev’ and maximum yellow colour (b*=48.8) in hybrid ‘Badshah’. The chroma (C*= 57.16), ascorbic acid (40.22 mg100 g-1), non-reducing sugar (1.62%) and lowest hue angle (ho=38.83) werefound maximum in hybrid ‘Shahanshah’. The maximum heritability (broadsense) estimates were noted for total sugar (100%) and non-reducing sugar(100%). The study depicted the scope of further improvement of these traitsthrough selection procedure and these genotypes could be considered forfurther heterosis breeding programme for future improvement.
Keywords: Correlation coefficient; genotypes; heritability; tomato; variability